Recent developments and future trends in volunteered geographic information research. The case of OpenStreetMap. - Neis, Pascal; Zielstra, Dennis (MDPI, 2014)
User-generated content (UGC) platforms on the Internet have experienced a steep increase in data contributions in recent years. The ubiquitous usage of location-enabled devices, such as smartphones, allows contributors to share their geographic information on a number of selected online portals. The collected information is oftentimes referred to as volunteered geographic information (VGI). One of the most utilized, analyzed and cited VGI-platforms, with an increasing popularity over the past few years, is OpenStreetMap (OSM), whose main goal it is to create a freely available geographic database of the world. This paper presents a comprehensive overview of the latest developments in VGI research, focusing on its collaboratively collected geodata and corresponding contributor patterns. Additionally, trends in the realm of OSM research are discussed, highlighting which aspects need to be investigated more closely in the near future.
Keywords: Kartographie; Geographie; Datensammlung; Datenbank; Partizipation; Kommunikationsmedien; Methode; Geodaten; Geoinformationssystem; User Generated Content; OpenStreetMap